The effect of flood on changing water quality parameters in Zarrin-Gol River, Golestan province - Mojtaba Ghareh Mahmoodlu; Nader Jandaghi; Mohammad Gholizade (مخاطرات محیط طبیعی, 2022)
To investigate the flood effect on changing the Zarrin-Gol water quality parameters, water was sampled from five stations on the river in three periods before, during, and after a flood and then some physicochemical parameters were determined. F-test was used to compare and determine the statistical difference between the qualitative parameters. Then, the hydrogeochemical changes of the river, effective factors in controlling the chemical composition as well as the dominant processes of the river water were determined. Finally, saturation indices were used to predict the possibility of precipitation/dissolution of some carbonate and evaporative minerals in all three periods. Results revealed that during the flood, chloride, and sodium ions were predominant ions in water and the most changes at different times were related to these two ions. The predominant water type in the periods before and after the flood was Mg-HCO3. Based on the Piper and Durov diagrams, most pre- and post-flood samples have facies of recharge areas. While, during the flood, with the abundance of chloride and sulfate ions in the water, composite facies prevail, and TDS at this time is almost three times before it occurs. Based on the accumulation, distribution, and orientation of the samples on the Gibbs diagram, the main factor controlling the water chemistry of the Zarringol river in all three periods is the chemical weathering of the minerals that form the basin rocks. Also, based on the results of ionic ratios, some evaporative minerals dissolution such as gypsum simultaneously with the phenomenon of cation exchange is one of the dominant hydrogeochemical processes during floods. While in most samples before and after the flood, the reverse ion exchange process is predominant. According to the results of bivariate diagrams, the main source of salinity of the Zarringol river is the dissolution of evaporative minerals (such as halite) belonging to the Mubarak Formation.